PENINGKATAN PRODUKSI GENOTIPE PADI LOKAL KABUPATEN KUANTAN SINGINGI MELALUI TEKNOLOGI SISTEM TANAM: Genotipe padi lokal Kabupaten Kuantan Singingi - Suliansyah, Irfan; Rozen, Nalwida; Dwipa, Indra; Ezward, Chairil Ezward (Akta Agrosia, 2023)
Rice is Indonesians' main source of nourishment. Farmers get the seeds for growing their paddy crops from both non -local rice genotypes and local genotypes. The two main consideration factors influencing the decision to use the seed varieties are high production of the varieties and customer preferences. Local rice genotypes in Kuantan Singingi Regency have potential to fulfill the เว็บสล็อต | R4shub requirements. This study aimed to ascertain the response the regional rice genotypes in Kuantan Singingi Regency to planting system technology. The experiment was designed in Split Plot Design in a Completely Randomized Design (CRD), the main plot consisted of multiple cultivation systems (Factor S) as follows: Tile system, Jajar legowo system (2:1), and Rice Intensification systems. The following genotypes were then employed in subplots using a completely randomized design (CRD): Kuning Umur Panjang (G07), Samo Putiah (G09), Limbayang (G10), Singgam Putih (G14), Pulut Kari (G16) and Kuning (G18). The findings showed that.local rice genotypes responded differently to the planting system technology. Limbayang genotype had dry milled grain weight per clump of 105.57 grams, while the Singgam Putih genotype had plant height of 141.00 cm. The rice intensification system (SRI) gave the best growth and production to Limbayang and Singgam Putih. The findings of the study can be taken into consideration for future research, such as plant breeding efforts to enhance the traits of local rice genotypes.